IMPROVING COMMUNITY SKILLS IN HANDLING CORPSES: EFFORTS TO MAINTAIN COMMON HONOR AND HEALTH - Rosyid, Abdul; Rahman, Arif; Wijaya, Candra; Wardana, Febri (STAI Al-Hidayah Bogor, 2024)
The Funeral Care Training in Ciampea Village aims to enhance the community's skills in handling the deceased in accordance with Islamic law and health protocols. This program focuses on improving the understanding and practical skills related to the proper procedures of funeral care, including washing the body, using the shroud, performing the funeral prayer, and proper burial. Additionally, this training seeks to strengthen the community's adherence to religious teachings and raise awareness about the importance of maintaining public health during the funeral process. The training results show a significant improvement in participants' understanding and skills, reflected in more accurate funeral care practices that align with Islamic law. Participants also actively disseminate the knowledge they gained to the community through lectures, teaching at religious schools, and social media. This program not only improves the quality of funeral care but also strengthens mutual respect and enhances health awareness within the community. Thus, this training contributes to creating a more respectful, healthy, and Islamically compliant funeral process